Gap Junctions in Leiomyomas and the Human Female Reproductive Tract - Christman, Gregory M. (Seminars in Reproductive Medicine, 2015)
The aim of the study was to critically examine existing data on the contribution of gap junctions to the function of the female reproductive tract and their role in cancer and benign gynecologic disease such as uterine leiomyomas and to evaluate the potential for clinical applications of gap junction intercellular communication (GJIC) in the treatment of diseases of the female reproductive tract. Gap junction proteins are present in all organs of the female reproductive tract. GJIC is vital to folliculogenesis, embryo implantation, and vascular changes associated with pregnancy and synchronization of uterine contractions of parturition. Loss of GJIC is associated with malignancy, and therapeutic restoration of GJIC reduces tumor growth and reverses chemotherapy resistance. GJIC is critical for various cell and tissue functions including the function of the female reproductive tract. Exploitation of the properties of GJIC may lead to novel treatments for both benign and malignant gynecologic diseases. GJIC is critical for various cell and tissue functions including specialized functions of the female reproductive tract and potential maintenance of the benign behavior of uterine leiomyomas.
Keywords: gap junctions; connexin; intercellular communication; leiomyomas